THE EFFECT OF USING PICTIONARY GAMES ON STUDENTS’ENGLISH VOCABULARY - Ayu, Rianda Rita; Sofian, Sofian; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe paper discusses the effectiveness of using Pictionary game to increase students? English vocabulary at the seventh grade students of SMP Kemala Bhayangkari Pontianak. The aim of this research was to know whether teaching vocabulary by using pictionary game was effective to the seventh  grade students? .The research method was pre- experimental research with one group pretest-posttest design. The sample was the seventh grade students that consisted of 22 students. The data was collected using measurement technique. The result of this research is analyzed by t-test. The t-ratio 9.58 was higher than the t-critical that was 2.093 on table distribution with ? =0.05. Therefore, the alternative hypothesis (Ha) which stated ?Teaching Vocabulary by Using Pictionary Game to seventh grade students of  Kemala Bhayangkariof JuniorHigh School Pontianak effects the students vocabulary achievement significantly? was accepted. It showed that Pictionary Game affect significantly on students? English vocabulary achievement.Keywords : Pictionary game, vocabulary